(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
Bachground: Ectopic thyroid is a rare entity resulting from maldescent of the thyroid gland & can be found anywhere between the foramen cecum & the normal pretracheal position of the thyroid gland, as well as in distant places such as the mediastinum and the subdiaphragmatic organs. Although most cases are asymptomatic, obstructive symptoms may appear. Any disease affecting the thyroid gland may also involve the ectopic thyroid, including malignancy. Hypothyroidism is frequent but hyperthyroidism is an exceptionally rare finding. The clinician must distinguish between ectopic thyroid and metastatic deposits emerging from an orthotopic gland, as well as other benign or malignant masses. Thyroid scintigraphy plays the most important role in diagnosing ectopy, but ultrasonography contributes as well. Treatment is indicated in the presence of symptoms & consists initially of full replacement thyroid hormone therapy. Severe or unresponsive cases require excision. Case reports: We present here two case reports & review of the literature. Conclusion: This review provides current understanding about the wide clinical spectrum of this rare condition, optimal diagnostic approach, differential diagnosis, and management strategies. DOI: http://dx.doi.org/10.3329/bjo.v18i2.12016 Bangladesh J Otorhinolaryngol 2012; 18(2): 193-199